Differences of Positive Linear Operators on Simplices - Ana-Maria Acu; Gülen Başcanbaz-Tunca; Ioan Rasa (Journal of Function Spaces)
The aim of the paper is twofold: we introduce new positive linear operators acting on continuous functions defined on a simplex and then estimate differences involving them and/or other known operators. The estimates are given in terms of moduli of smoothness and K-functionals. Several applications and examples illustrate the general results.